1988
DOI: 10.1128/aem.54.1.264-267.1988
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Clostridium perfringens L forms with shuttle plasmid DNA

Abstract: L-form (L-phase) cultures of Clostridium perfringens were tested for their transformability with plasmid DNA. Three L-form strains were transformable, but one, strain L-13, was superior to the others. This strain was easily and reproducibly transformed with previously described shuttle vectors which were derived from either C. perfringens or Escherichia coli. Strain L-13 was transformable by a variety of methods, and a new micromethod worked well under both aerobic and anaerobic conditions. The maximal number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…We found that cultures of L-13 in BHIS survived only 2 to 3 days at 37°C or room temperature, 4 to 5 days at 4°C, and 3 to 4 weeks at 4°C in BHIS with 0.25% agar (the semisolid medium described by Mahony et al [7]). Chopped-meat cultures (4) of L-13 were prepared by withdrawing 5 ml of the Trypticase liquid medium from a chopped-meat tube and replacing the liquid with 5 ml of an overnight culture of L-13 in BHIS.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…We found that cultures of L-13 in BHIS survived only 2 to 3 days at 37°C or room temperature, 4 to 5 days at 4°C, and 3 to 4 weeks at 4°C in BHIS with 0.25% agar (the semisolid medium described by Mahony et al [7]). Chopped-meat cultures (4) of L-13 were prepared by withdrawing 5 ml of the Trypticase liquid medium from a chopped-meat tube and replacing the liquid with 5 ml of an overnight culture of L-13 in BHIS.…”
mentioning
confidence: 81%
“…This paper describes the construction and performance of a shuttle plasmid (pHR106) which contains a chloramphenicol resistance marker gene and a set of unique cloning sites and which transforms L-phase C. perfringens L-13 with ease and reliability. The accompanying paper by Mahony et al (7) presents the background of strain L-13 and data on its transformation.…”
mentioning
confidence: 99%
“…Recently, there has been a renewed interest in L-form bacteria. This has arisen because of their apparent ability to associate with plant cells (Jones & Paton 1973;Aloysius & Paton 1984;Paton 1987) and in the case of Clostridium perfringens, the increased ease of their genetic transformation compared with the cell-walled form (Mahony et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Squires et al (19) constructed shuttle vectors and demonstrated their transferability into Escherichia coli and L-phase variants of C. perfringens. C. perfringens L-phase variant transformation was described by Heefner et al (9) and, more recently, Mahony et al (12). Roberts et al (16) recently described an E. coli-C. perfringens shuttle vector (pHR106) which was transformed into L-phase variants of C. perfringens.…”
mentioning
confidence: 99%